The quality of sputum smear microscopy diagnosis of pulmonary tuberculosis in Dar es Salaam, Tanzania - Mfinanga, G S; Ngadaya, E; Mtandu, R; Mutayoba, B; Doulla, B; Kimaro, G; Chonde, T M; Ngowi, P; Mfaume, S; Kilale, A M; Egwaga, S; Kitua, A Y (Tanzania Journal of Health Research, 2008)
No Abstract. Tanzania Health Research Bulletin Vol. 9 (3) 2007: pp. 164-168